2010
DOI: 10.1089/ten.tea.2008.0596
|View full text |Cite
|
Sign up to set email alerts
|

Novel Embryoid Body–Based Method to Derive Mesenchymal Stem Cells from Human Embryonic Stem Cells

Abstract: Application of human embryonic stem cells (hESCs) to stem-cell therapy is not feasible because of the risk of tumorigenicity and rejection. In contrast, human mesenchymal stem cells (hMSCs) are free from the risk of tumorigenicity and also have immune privilege. However, hMSCs obtained from adults have infinite variety in terms of the biological characteristics and functionality. We report here a new derivation method of hMSCs from hESCs. The derivation of hMSCs from three different hESC lines (SNUhES3, CHA3-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 23 publications
1
68
0
Order By: Relevance
“…The generation from hESCs of several progenitor populations with limited mesodermal potential has been previously described using combinations of markers of hematoendothelial (CD34 and PDGFR-α), cardiovascular (KDR + CD117 − cells), and mesenchymal (CD73) differentiation (3,4,6,21). We now demonstrate that day 3.5 CD326 − CD56 + cells represent the earliest multipotent mesodermal progenitors reported to date, being generated before the appearance of the previously described populations and capable of giving rise to all of the above progenitor cell phenotypes and related mesodermal lineages.…”
Section: Discussionmentioning
confidence: 99%
“…The generation from hESCs of several progenitor populations with limited mesodermal potential has been previously described using combinations of markers of hematoendothelial (CD34 and PDGFR-α), cardiovascular (KDR + CD117 − cells), and mesenchymal (CD73) differentiation (3,4,6,21). We now demonstrate that day 3.5 CD326 − CD56 + cells represent the earliest multipotent mesodermal progenitors reported to date, being generated before the appearance of the previously described populations and capable of giving rise to all of the above progenitor cell phenotypes and related mesodermal lineages.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of attempts to generate osteo-and chondroprogenitors (also known as bone marrow-derived mesenchymal stem cells [MSCs]) from embryonic stem cells (ESCs) [1][2][3][4][5][6][7][8][9][10] and iPSCs [11][12][13][14]. However, there are three broad limitations in performing these types of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that MSCs can be derived from hESCs [9][10][11] that these differentiated cells expressed MSCs surface markers [2,9]. Also, our preliminary data showed hESCs derived MSCs (hESCs-MSCs) with fibroblast-like morphology ( Figure 1) expressed CD105 and FIBRONECTIN as MSC specific markers (unpublished data; Figure 1).…”
Section: Introductionmentioning
confidence: 65%